Portraits in silicon - Slater, Robert, 1943-2014 (MIT Press, 1987)
Short biographies of: Charles Babbage, Alan Turing, John von Neumann, Claude Shannon, Konrad Zuse, John V. Atanasoff, John V. Mauchly, J. Presper Eckert, Howard Aiken, Jay W. Forrester, Thomas J. Watson, Sr., William Norris, H. Ross Perot, William Shockley, Robert Noyce, Jack Kilby, Marcian E. (Ted) Hoff, Gene Amdahl, Seymour Cray, Gordon Bell, Grace Murray Hopper, John Backus, John Kemeny, Thomas Kurtz, Gary Kildall, William Gates, Dennis Ritchie, Kenneth Thompson, Daniel Bricklin, Nolan Bushnell, Steven Jobs, Adam Osborne, William Millard, Donald Knuth.
Includes index.
Keywords: Computer engineers -- Biography.; Computers -- History.; Computer industry -- History.; Industrialists -- Biography.; elektronické knihy; electronic books